2022
DOI: 10.3390/s22072704
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning in Injection Molding: An Industry 4.0 Method of Quality Prediction

Abstract: One of the essential requirements of injection molding is to ensure the stable quality of the parts produced. However, numerous processing conditions, which are often interrelated in quite a complex way, make this challenging. Machine learning (ML) algorithms can be the solution, as they work in multidimensional spaces by learning the structure of datasets. In this study, we used four ML algorithms (kNN, naïve Bayes, linear discriminant analysis, and decision tree) and compared their effectiveness in predictin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Furthermore, ML models can also be utilized to predict the quality of polymers, for example, of acrylonitrile butadiene styrene parts produced via injection molding. [ 159 ] The input features used in the models were customized integrals over the cavity pressure curves and the generated parts were classified as “undercompensated,” “acceptable,” or “overcompensated.” Accuracies of about 90% were achieved using decision tree‐based models.…”
Section: Processing and Fabricationmentioning
confidence: 99%
“…Furthermore, ML models can also be utilized to predict the quality of polymers, for example, of acrylonitrile butadiene styrene parts produced via injection molding. [ 159 ] The input features used in the models were customized integrals over the cavity pressure curves and the generated parts were classified as “undercompensated,” “acceptable,” or “overcompensated.” Accuracies of about 90% were achieved using decision tree‐based models.…”
Section: Processing and Fabricationmentioning
confidence: 99%
“…Treebased algorithms, regression-based algorithms, or neural networks are applied to perform classifications or regressions [13] [14]. An interesting approach is described in [15], where the use of sensor data for prediction models is outlined. The authors identified the cavity pressure as essential for quality, which is why sensor data provide important information.…”
Section: Introduction and Motiv A T Ionmentioning
confidence: 99%
“…Therefore, finding a relation between product quality and process parameters is a non-trivial task that requires a comprehensive approach, which often involves a combination of sensoring and information techniques [ 6 ]. Statistical analysis [ 7 , 8 ] and artificial intelligence (AI) [ 9 ], especially machine learning (ML) [ 10 , 11 , 12 ], are used more and more frequently today for the process optimization and quality control of industrial manufacturing processes. However, these methods are data-driven and often do not consider the physical aspects of injection molding.…”
Section: Introductionmentioning
confidence: 99%